Development of Novel Faster-Dissolving Microneedle Patches for Transcutaneous Vaccine Delivery - Akihiko Ono; Sayami Ito; Shun Sakagami; Hideo Asada; Mio Saito; Ying-Shu Quan; Fumio Kamiyama; Sachiko Hirobe; Naoki Okada (MDPI AG, 2017)
Microneedle (MN) patches are promising for transcutaneous vaccination because they enable vaccine antigens to physically penetrate the stratum corneum via low-invasive skin puncturing, and to be effectively delivered to antigen-presenting cells in the skin. In second-generation MN patches, the dissolving MNs release the loaded vaccine antigen into the skin. To shorten skin application time for clinical practice, this study aims to develop novel faster-dissolving MNs. We designed two types of MNs made from a single thickening agent, carboxymethylcellulose (CMC) or hyaluronan (HN). Both CMC-MN and HN-MN completely dissolved in rat skin after a 5-min application. In pre-clinical studies, both MNs could demonstrably increase antigen-specific IgG levels after vaccination and prolong antigen deposition compared with conventional injections, and deliver antigens into resected human dermal tissue. In clinical research, we demonstrated that both MNs could reliably and safely puncture human skin without any significant skin irritation from transepidermal water loss measurements and ICDRG (International Contact Dermatitis Research Group) evaluation results.